The prevalence of sarcopenia and relationships between muscle and bone in ageing West‐African Gambian men and women. Issue 5 (16th September 2018) - Zengin, Ayse; Jarjou, Landing M.; Prentice, Ann; Cooper, Cyrus; Ebeling, Peter R.; Ward, Kate A.
Abstract: Background: The rapidly rising ageing population in low and middle‐income countries (LMIC) will lead to a concurrent increase in musculoskeletal diseases. Sarcopenia is a disease caused by progressive loss of skeletal muscle mass and strength, leading to adverse outcomes including frailty, falls, fractures, and premature mortality. We investigated the prevalence of sarcopenia, assessed the suitability of current diagnostic guidelines and explored muscle–bone relationships in ageing men and women from rural Gambia. Methods: A total of 249 women and 239 men aged 40–75+ years were recruited. Body composition was measured using dual energy X‐ray absorptiometry. Comparisons of the Foundations for the National Institutes of Health (FNIH) and European Working Group On Sarcopenia (EWGSOP) definitions of sarcopenia to define prevalence and to identify poor physical capability were determined. Functional ability was assessed by jumping mechanography to calculate lower limb muscle force and power; grip strength was assessed by a hand dynamometer. Peripheral quantitative computed tomography was used to assess muscle–bone relationships. Results: The prevalence of sarcopenia in Gambian men and women significantly varied depending on the definition used; in men 20% and 19% and in women 45% and 10% for FNIH and EWGSOP, respectively. The FNIH appendicular lean mass cut‐off had greatest sensitivity and specificity in identifying low functional ability in Gambian adults. Muscle force was positively associated with measures of tibial bone size, strength, and mineral content. Conclusions: The variation in the prevalence of sarcopenia depends on the definition used and highlights the importance of measuring functional capability across ethnic populations.